School Community Preparedness in Reducing The Risk of Earthquake and Tsunami Disasters in Pesisir Selatan Regency - Afrida, Yola; Manawanui, Robert (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research is to analyze school community preparedness in reducing the earthquake and tsunami in Pesisir Selatan Regency especially in the red zone area. The type of this research is descriptive by using observation, interview, and questionnaire in collecting data. Data were analyzed by using percentage formula to determine the respondents’ tendency. The sample is determined by utilizing a purposive sampling technique to select the school and proportional random sampling technique to select the respondent. The results of the research indicated that: 1) The students’ knowledge of Senior High School 1 Koto XI Tarusan about disaster-prone areas around 77,14% are categorized as being, 2) The parameters of disaster prepared school policy around 11,42% is categorized as low, 3) The parameters of the emergency response plan about 20% are categorized as very low, there is not a direction for evacuation route or evacuation map yet, 4) The parameters of resources mobilization about 40% are categorized as very low. Based on the calculation of indicator achievement level, it can be concluded that overall schools in Pesisir Selatan Regency have not implemented the school program of disaster preparedness yet whereas it is located in the disaster-prone area of ​​the earthquake and Tsunami. This research recommends the establishment of disaster preparedness school programs for the needs of serious disaster mitigation efforts on the part of policymakers. These efforts should be done appropriately with the program and continuous futures. In the efforts are given various innovative activities that must be done, such as periodic socialisation and disaster response simulations, and provision of facilities and infrastructure.